2017
DOI: 10.18632/oncotarget.21440
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of chemerin is associated with poor clinical outcome in acute myeloid leukemia

Abstract: Chemerin is dysregulation in numerous solid cancers. However, only little is known about the role of chemerin in acute myeloid leukemia (AML). In this study, we aimed to investigate the expression and clinical significance of recently described chemerin in acute myeloid leukemia (AML). The expression of chemerin in 149 patients with de novo AML and 35 normal controls was quantified by Real-time quantitative PCR (RQ-PCR). Chemerin was down-expressed in AML compared with controls (P=0.042). A receiver operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The same group performed a cohort study of 149 patients, 32 of whom had high chemerin expression and 117 of whom had low expression, with no significant variability in certain gene mutations, white blood cell count, platelets, and hemoglobin, and found that patients with low chemerin expression correlated with poorer overall survival. Moreover, multivariate analysis on parameters such as age, various gene mutations, chemerin expression, karyotypic classifications, and white blood cell count verified that chemerin was independently able to prognosticate AML patients, while univariate analysis of chemerin expression levels showed that high chemerin expression was associated with positive prognosis ( 22 ). In terms of chemerin receptor expression levels (independent of associations between chemerin expression and clinical outcome), a different group showed that CCRL2 was overexpressed in AML, identifying the non-classically signaling chemerin receptor as a potential therapeutic target, along with other GPCRs that were also overexpressed ( 37 ).…”
Section: Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…The same group performed a cohort study of 149 patients, 32 of whom had high chemerin expression and 117 of whom had low expression, with no significant variability in certain gene mutations, white blood cell count, platelets, and hemoglobin, and found that patients with low chemerin expression correlated with poorer overall survival. Moreover, multivariate analysis on parameters such as age, various gene mutations, chemerin expression, karyotypic classifications, and white blood cell count verified that chemerin was independently able to prognosticate AML patients, while univariate analysis of chemerin expression levels showed that high chemerin expression was associated with positive prognosis ( 22 ). In terms of chemerin receptor expression levels (independent of associations between chemerin expression and clinical outcome), a different group showed that CCRL2 was overexpressed in AML, identifying the non-classically signaling chemerin receptor as a potential therapeutic target, along with other GPCRs that were also overexpressed ( 37 ).…”
Section: Cancersmentioning
confidence: 99%
“…As expected, these recent studies have confirmed the notion that chemerin's functions in cancer are context driven. In some cancer types [e.g., glioblastoma, mesothelioma, neuroblastoma, squamous cell carcinoma of the esophagus, and squamous cell carcinoma of the oral tongue (SCCOT)], chemerin is upregulated ( 16 22 ). In most cancer types [e.g., acute myeloid leukemia (AML), adrenocortical carcinoma (ACC), breast cancer, Ewing sarcoma, hepatocellular carcinoma, melanoma, non-small cell lung cancer (NSCLC), prostate cancer, and squamous cell carcinoma of the skin] chemerin is downregulated, likely via hypermethylation of RARRES2 ( 15 , 19 , 23 – 28 ) (Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with AML, low chemerin expression correlated with poorer overall survival. It was shown that chemerin was independently able to prognosticate AML patients, and high chemerin expression was associated with positive prognosis [85]. Chemerin receptor CCRL2 was reported to be overexpressed in AML cells and was suggested to be a potential therapeutic target [86].…”
Section: Chemerin and Cancermentioning
confidence: 99%
“…Chemerin expression is different depending on the tumor type 10 . Chemerin has been shown to be downregulated compared to normal tissue counterparts in hepatocellular carcinoma 11 , melanoma 12 , non-small cell lung cancer 13 , adrenocortical carcinoma 14 , prostate cancer 15 , and acute myeloid leukemia 16 . In contrast, chemerin is significantly upregulated in glioblastoma 17 , mesothelioma, and squamous cell carcinoma 18 .…”
Section: Introductionmentioning
confidence: 99%